Impact of internal controls on execution of payroll system : A case study of Ministry of Finance and Economic Affairs – Zanzibar (MoFEA) - Ahmada, Ridhwan I. (Mzumbe University, 2024)
A Dissertation Submitted to the School of Business in Fulfillment of the Requirements for Award of the Degree of Master of Science in Accounting and Finance (MSc A&F) of Mzumbe University